2007
DOI: 10.1007/s11262-007-0098-8
|View full text |Cite|
|
Sign up to set email alerts
|

Transmembrane protein polymorphisms and resistance to T-20 (Enfuvirtide, Fuzeon®) in HIV-1 infected therapy-naive seroconverters and AIDS patients under HAART-T-20 therapy

Abstract: The human immunodeficiency virus type 1 fusion inhibitor T-20 (Enfuvirtide, Fuzeon) has recently been introduced into clinical practice. T-20 in combination with HAART efficiently inhibits HIV-1 replication, however T-20 resistance has been reported and the number of confirmed resistant-associated mutations is growing. In this study we aimed to analyze HIV-1 gp41 transmembrane protein (TM) variability and primary resistance to T-20 in plasma viruses from 10 HIV-1 subtype B infected homosexuals. Nine out of ten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…Two groups reported transmission of viruses with resistance mutations to the fusion inhibitor enfuvirtide. 40,41 However,…”
Section: Resultsmentioning
confidence: 99%
“…Two groups reported transmission of viruses with resistance mutations to the fusion inhibitor enfuvirtide. 40,41 However,…”
Section: Resultsmentioning
confidence: 99%
“…In particular, the conserved FLGFL motif at positions 8-12 has been reported to be essential for fusogenic activities (5). Recent studies have shown that mutations with a polar residue inserted into this motif, such as V2E and L9R substitutions, reduced its fusogenic activity significantly (6). …”
mentioning
confidence: 99%
“…Fourthly, in the recent years, considerable numbers of peptide drugs have been approved or are under clinical studies for a wide variety of diseases such as AIDS and other malignancies. Several selected successful therapeutic peptides isolated from phage display, which have been approved or are under clinical studies, are listed along with their functions, indications, and manufacturers .…”
Section: Applications Of Bacteriophagesmentioning
confidence: 99%